Association of mandatory seat belt use legislations intervention by traffic police with changes in road traffic injuries in Iran - Movahedi, M; Soori, H; Nasermoadeli, A; Ainy, E; Mehmandar, M R; Nejhad, M R Masoodei; Abady, H R Hatam; Azari, M Rezazadeh; Mahfozphoor, S; Vafaee, R (Injury prevention, 2010)
Background and Objective This study investigated the efficacy of mandatory seat belt use legislation on reducing traffic injuries and the intensity of road traffic injuries (RTIs). Materials and Methods Data on RTIs from 1 year before till 2 years after the implementation of mandatory seat belt use legislation were obtained from the police department. After data cleaning and stratification RTIs and moralities from 1 year before till 2 year after the implementation of mandatory seat belt use legislations was compared with those in year prior to the intervention. Results After the implementation of the mandatory seat belt use, traffic mortalities consisted of 13.3% of all RTIs in the year prior to the implementation, while this proportion decreased to 9.9% and 11.5% in the first and second years after the implementation, respectively. The trend of mortality reduction was not consistent for seat belt use, as we observed a slight increase in the proportion of moralities in the second year after the implementation of mandatory seat belt use, though they did not reach the levels for before implementation of those laws. Conclusion Our findings suggested that the mandatory of seat belt use was efficient in reduction of intensity of RTIs and it was also efficient in reducing the crude number of RTIs. However, in the second year after the implantation the efficiency of this intervention reduced.